Assessment of the addition of the copepod Apocyclops panamensis on the super-intensive grow-out of Penaeus vannamei with biofloc system - Krummenauer, Dariano; Ramiro, Bianca de Oliveira; Hoffling, Flávia Banderó; Miyai, Caio [UNESP]; Urick, Stephen; Monserrat, José Maria; Wasielesky, Wilson; Schwarz, Michael H.; Pimentel, Otávio Augusto Lacerda Ferreira (Springer Nature, 2025)
The aim of this study was to evaluate the influence of the addition of the copepod Apocyclops panamensis on the super-intensive culture of Penaeus vannamei with a biofloc system, including evaluation of the nitrification process, shrimp growth, and color pattern of the shrimp produced. A grow-out trial was conducted over 70 days assessing the following treatments: CW + Copepod (clear water inoculated with copepods), BFT + Copepod (biofloc system inoculated with copepods), and BFT (biofloc system without copepods). P. vannamei post larvae (0.056 ± 0.00 g) was stocked at a density of 500 shrimp m−3. The CW + copepod and BFT + copepod treatments received copepod addition weekly at a density of 5 organisms mL−1. The nitrogenous compound patterns were monitored every 3 days. At the end of the experiment, shrimp performance and the color aspects of the thawed and cooked shrimp were evaluated. Total ammonia nitrogen and nitrate were higher in the BFT + Copepod and BFT than in the CW + Copepod. Nitrite was higher in the BFT than in the others. The shrimp final weight did not differ significantly among the treatments. Survival was higher in the CW + Copepod. Thawed shrimps were less yellowish in the biofloc treatments than in the clear water treatments. Cooked shrimps were more reddish in the BFT + Copepod. Our findings indicated that the addition of the copepod A. panamensis in a super-intensive grow-out of P. vannamei can be considered an alternative to improve the culture, since it does not limit shrimp growth, improves the control of nitrite, and the color aspects of thawed and cooked shrimp.